Pengaruh Media Tanam dan Intensitas Naungan terhadap Pertumbuhan Bakau Minyak (Rhizophora apiculata) - Cecep Kusmana; Diah Ayu Puji Lestari (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2021)
Damage to mangrove forests has reduced the size forest area and the diversity of mangrove species. Improvement of mangrove forests require seeds with good growth and resistant to pests and diseases. The shade levels and growing media is a factor that affects plant growth. The purpose of this study was to analyze the effect of growing media and shade level on the growth of bakau minyak (R. apiculata). The study was conducted for 12 weeks and used a complete randomized design to analyze the data. The first factor was the growing media (A) with 3 levels of treatment, namely mudsoil (A0), mud and compost (A1), and mud, sand and compost (A2). The second factor was the shade level (N) with 3 levels treatment, namely the shade intensity 0% (N0), 50% (N1), and 70% (N2). The result of this study indicate that the shade intensity has a significant effect on the growth of Rhizophora apiculata, and the growing medium does not significantly affect the growth of Rhizophora apiculata. The best shade intensity for growth of R. apiculata is 0% (N0). Keywords: growing media, mangrove forest, rehabilitation, Rhizophora apiculata, shade level